Thankfully and Joyfully Receiving the Father and Becoming a Christian - Aroney, Matt (Religions, 2023)
Kierkegaard’s status as a virtue ethicist is a current discussion topic. Of vital importance to the question is not whether Kierkegaard’s work contains some use of virtues but where they fit in relation to his stated aims of showing someone how to become a Christian. This article seeks to demonstrate that the virtues of Thankfulness and Joy are deployed in Kierkegaard’s discourses to lead people into a relationship with God the Father. The virtues are ultimately gifts from the Triune God that lead back to a life with the Triune God. Thus, though Kierkegaard at times fits the mould of a virtue ethicist, his teleology differs in its focus on both the self and relationship with God.